Glucose-lowering effect of berberine on type 2 diabetes: A systematic review and meta-analysis - Xie, Wenting; Su, Fugui; Wang, Guizhong; Peng, Zichong; Xu, Yaomin; Zhang, Yi; Xu, Ningning; Hou, Kaijian; Hu, Zhuping; Chen, Yan; Chen, Rongping (Frontiers in Pharmacology, 2022)
Background: Traditional insulin secretory agents such as sulfonylureas and glinides are commonly used to treat type 2 diabetes, but have side effects of hypoglycemia. In recent years, researchers have discovered that berberine can promote insulin secretion without causing hypoglycemia, because the glucose-lowering effects of berberine are only under hyperglycemic conditions. In order to shed light on the glucose-lowing effects of berberine in type 2 diabetes with different baseline fasting plasma glucose (FPG) and glycosylated hemoglobin (HbA1c), we conducted a meta-analysis of randomized controlled trials. Methods: We searched eight databases, which included PubMed, EMBASE, Web of Science, the Cochrane Library, and the Chinese databases such as Sino-Med, CNKI, Wanfang Database, and VIP Database, for randomized controlled trials, with berberine as the intervention and patients with type 2 diabetes mellitus as subjects, published up until November 2021. We analyzed the glucose-lowing effects of berberine, including its effects on FPG, HbA1c and 2-hour plasma blood glucose (2hPBG), by calculating weighted mean differences (WMD) and 95% confidence interval (CI). To assess the safety of berberine, we analyzed the incidence of total adverse events and hypoglycemia by calculating relative risk (RR) and 95% CI. Results: Thirty-seven studies involving 3,048 patients were included in the meta-analysis. The results showed that berberine could reduce FPG (WMD = -0.82 mmol/L, 95% CI (-0.95, -0.70)), HbA1c (WMD = -0.63%, 95% CI (-0.72, -0.53)), and 2hPBG (WMD = -1.16 mmol/L, 95% CI (-1.36, -0.96)), with all results being statistically significant. Subgroup analyses revealed that the glucose-lowering effect of berberine was associated with baseline mean FPG and HbA1c. In addition, berberine alone or in combination with oral hypoglycemic agents (OHAs) in the treatment of T2DM did not significantly increase the incidence of total adverse events (RR = 0.73, 95% CI (0.55, 0.97), P = 0.03) and the risk of hypoglycemia (RR = 0.48, 95% CI (0.21, 1.08), P = 0.08). Conclusion: Berberine has a glucose-lowering effect, which is related to the baseline FPG and HbA1c levels of patients. Treatment with berberine may be safe since it does not increase the incidence of total adverse events and the risk of hypoglycemia.